1994
DOI: 10.1039/an9941900833
|View full text |Cite
|
Sign up to set email alerts
|

Novel, reagentless, amperometric biosensor for uric acid based on a chemically modified screen-printed carbon electrode coated with cellulose acetate and uricase

Abstract: Amperometry in stirred solution has been used for the systematic evaluation of modified screen-printed carbon electrodes (SPCEs) with a view to developing a reagentless biosensor for uric acid. The developed system consists of a base cobalt phthalocyanine (CoPC) electrode tailored to the electrocatalytic oxidation of H2O2 by means of a cellulose acetate (CA)-uricase bilayer. Uricase was immobilized by drop-coating the enzyme onto the CA membrane covering the CoPC-SPCE. The device exploits the near-universal H2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0
2

Year Published

2000
2000
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(28 citation statements)
references
References 10 publications
0
26
0
2
Order By: Relevance
“…It has previously been shown that our unmodi®ed SPCEs demonstrate good electron transfer characteristics and have been successfully employed for the measurement of triclosan (a phenolic species) in mouthwash and toothpaste products by stripping voltammetry [6]. The same electrodes were applied to the oxidative measurement of paracetamol [7] and uric acid [8]. It should also be noted that other workers have successfully used the same ink, containing a ligand, for the fabrication of a sensor for Ni [9].…”
Section: Introductionmentioning
confidence: 93%
“…It has previously been shown that our unmodi®ed SPCEs demonstrate good electron transfer characteristics and have been successfully employed for the measurement of triclosan (a phenolic species) in mouthwash and toothpaste products by stripping voltammetry [6]. The same electrodes were applied to the oxidative measurement of paracetamol [7] and uric acid [8]. It should also be noted that other workers have successfully used the same ink, containing a ligand, for the fabrication of a sensor for Ni [9].…”
Section: Introductionmentioning
confidence: 93%
“…Other methods includes, high performance liquid chromatography on reversed phase columns along with detection by either UV absorbance or mass spectrometry (MS) [25]. Each of these methods involves multiple reaction steps including serum preparation, various sample preparation steps and eventually require either spectroscopic methods to identify the product [26,27] or an enzyme cascade technique which indirectly determines the concentration of the H 2 O 2 intermediate [28]. Also in these assays the blood sample has to be converted into denatured serum as coagulated blood particles tend to create erroneous detection signals.…”
mentioning
confidence: 99%
“…In the first approach the O 2 consumption or the H 2 O 2 formed is usually monitored while in the second the peroxidase consumption of H 2 O 2 produced in the enzymatic oxidation of uric acid is determined. However, the construction procedures described usually requires time consuming enzyme immobilization procedures [3,7,8], are of relative complex preparation or exhibit lack of robustness [4 -7, 9 -11], and are applied to real sample analysis in a manual batch fashion. Moreover the analytical benefits of the above-mentioned preparations is questionable since some of these electrodes are still capable to oxidize another analytes present in serum samples, or exhibit slow responses [3,4] and short useful lifetime [3,7,11].…”
Section: Introductionmentioning
confidence: 99%